2002
DOI: 10.1093/rheumatology/41.1.78
|View full text |Cite
|
Sign up to set email alerts
|

Serum matrix metalloproteinases and tissue inhibitors of metalloproteinases in different histological variants of rheumatoid synovitis

Abstract: The morphological appearance of rheumatoid synovitis and the serum MMP and TIMP-1 profile were correlated with the clinical activity of the disease, confirming the heterogeneity of RA. These associations also suggest that patients with different histological forms of RA might require different treatment regimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
62
2

Year Published

2004
2004
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 35 publications
5
62
2
Order By: Relevance
“…In the present study, this was observed with levels of serum MMP-3, and although it is disappointing that we did not demonstrate changes in levels of other biochemical markers with MTX therapy, the study was not designed to address this question and the number of patients receiving MTX was limited. Our findings regarding serum MMP-3 levels in patients treated with MTX are consistent with the results of other studies that have shown a decrease in circulating MMP-3 levels with conventional DMARD therapy (43,44) or biologic therapy (45)(46)(47).…”
Section: Young-min Et Alsupporting
confidence: 92%
“…In the present study, this was observed with levels of serum MMP-3, and although it is disappointing that we did not demonstrate changes in levels of other biochemical markers with MTX therapy, the study was not designed to address this question and the number of patients receiving MTX was limited. Our findings regarding serum MMP-3 levels in patients treated with MTX are consistent with the results of other studies that have shown a decrease in circulating MMP-3 levels with conventional DMARD therapy (43,44) or biologic therapy (45)(46)(47).…”
Section: Young-min Et Alsupporting
confidence: 92%
“…Association of the MMP-1-MMP-3 loci with disease activity Previous studies have shown significant correlations of MMP-1, and particularly MMP-3 serum levels with levels of inflammation in RA. 7,[9][10][11][13][14][15] In this study, we found significant correlations of MMP-1 and MMP-3 with the level of disease activity (DAS28 at baseline Figure 2 Relationship between MMP genotypes and circulating levels of MMPs. Panels (a-d) show serum levels of MMP-1 in patients with different genotypes of rs1799750, rs495366, rs679620 and rs3025058, respectively.…”
Section: Association Of Mmp-1-mmp-3 Loci With Circulating Levels Of Mmpsmentioning
confidence: 75%
“…Elevated levels of MMP-1 and -3 have been observed in patients with RA in both serum and synovial fluid, and are strongly associated with inflammation and joint destruction. [6][7][8][9][10][11][12][13][14][15][16][17][18][19] The genes for MMP-1 and -3 are both located on the long arm of chromosome 11, in a cluster together with seven other MMP members including MMP-7, -8, -10, -12 and -13. In recent years, functionally relevant and phenotype associated polymorphisms have been detected across the region of both genes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated serum levels of MMPs have been reported in, for example, polycystic kidney disease (19), systemic sclerosis (20), rheumatoid arthritis (21), and cancer. In some diseases, such as acute viral hepatitis, however, serum levels of MMPs are reduced (22).…”
mentioning
confidence: 99%